On the use of the p-q theory for harmonic currents cancellation with shunt active filter (2019)
Discussion and mathematical proof on necessary and sufficient conditions for the application of the p-q theory for compensating the harmonic currents consumed by non-linear load using a shunt active filter are presented. These conditions over instantaneous active and reactive powers were not addressed before and must be considered on the design of new control strategies based on p-q theory. Theoretical demonstration is proposed and an application example with simulations results is used to validate the theoretical results. © 2019 ADVANCES IN ELECTRICAL AND ELECTRONIC ENGINEERING.